Ruthenium Complexes With Piplartine Cause Apoptosis Through MAPK Signaling by a p53-Dependent Pathway in Human Colon Carcinoma Cells and Inhibit Tumor Development in a Xenograft Model - Baliza, Ingrid R. S.; Silva, Suellen L. R.; Santos, Luciano de S.; Neto, João H. Araujo; Dias, Rosane B.; Sales, Caroline B. S.; Rocha, Clarissa A. Gurgel; Soares, Milena B. P.; Batista, Alzir A.; Bezerra, Daniel P. (Frontiers in Oncology, 2019)
Ruthenium complexes with piplartine, [Ru(piplartine)(dppf)(bipy)](PF6)2 (1) and [Ru(piplartine)(dppb)(bipy)](PF6)2 (2) (dppf = 1,1-bis(diphenylphosphino) ferrocene; dppb = 1,4-bis(diphenylphosphino)butane and bipy = 2,2’-bipyridine), were recently synthesized and displayed more potent cytotoxicity than piplartine in different cancer cells, regulated RNA transcripts of several apoptosis-related genes, and induced reactive oxygen species (ROS)-mediated apoptosis in human colon carcinoma HCT116 cells. The present work aimed to explore the underlying mechanisms through which these ruthenium complexes induce cell death in HCT116 cells in vitro, as well as their in vivo action in a xenograft model. Both complexes significantly increased the percentage of apoptotic HCT116 cells, and co-treatment with inhibitors of JNK/SAPK, p38 MAPK and MEK, which inhibits the activation of ERK1/2, significantly reduced the apoptosis rate induced by these complexes. Moreover, significant increase in phospho-JNK2 (T183/Y185), phospho-p38α (T180/Y182) and phospho-ERK1 (T202/Y204) expressions were observed in cells treated with these complexes, indicating MAPK-mediated apoptosis. In addition, co-treatment with a p53 inhibitor (cyclic pifithrin-α) and the ruthenium complexes significantly reduced the apoptosis rate in HCT116 cells, and increased phospho-p53 (S15) and phospho-histone H2AX (S139) expressions, indicating induction of DNA damage and p53-dependent apoptosis. Both complexes also reduced HCT116 cell growth in a xenograft model. Tumor mass inhibition rates were 35.06, 29.71 and 32.03% for the complex 1 (15 μmol/kg/day), complex 2 (15 μmol/kg/day) and piplartine (60 μmol/kg/day), respectively. These data indicate these ruthenium complexes as new anti-colon cancer drugs candidates.